2019
DOI: 10.3847/1538-4357/ab4d4f
|View full text |Cite
|
Sign up to set email alerts
|

The Most Massive Galaxies with Large Depleted Cores: Structural Parameter Relations and Black Hole Masses

Abstract: Luminous spheroids (M V −21.50 ± 0.75 mag) contain partially depleted cores with sizes (R b ) typically 0.02 -0.5 kpc. However, galaxies with R b > 0.5 kpc are rare and poorly understood. Here we perform detailed decompositions of the composite surface brightness profiles, extracted from archival Hubble Space Telescope and ground-based images, of 12 extremely luminous "large-core" galaxies that have R b > 0.5 kpc and M V −23.50 ± 0.10 mag, fitting a core-Sérsic model to the galaxy spheroids. Using 28 "normal-c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
83
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(95 citation statements)
references
References 180 publications
(380 reference statements)
12
83
0
Order By: Relevance
“…Large-core galaxies are found to obey the same scaling relations between break radius and surface brightness or spheroid luminosity as normal core galaxies, as well as a log-linear break radius-SMBH mass relation, when a measurement is available (Dullo 2019). However, directly measured SMBHs are overmassive with respect to predictions from the M SMBH −L and the M SMBH −σ relations, with a more significant offset for the latter relation.…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…Large-core galaxies are found to obey the same scaling relations between break radius and surface brightness or spheroid luminosity as normal core galaxies, as well as a log-linear break radius-SMBH mass relation, when a measurement is available (Dullo 2019). However, directly measured SMBHs are overmassive with respect to predictions from the M SMBH −L and the M SMBH −σ relations, with a more significant offset for the latter relation.…”
Section: Introductionmentioning
confidence: 88%
“…Dullo & Graham 2012, 2014. Furthermore, it has been shown that adopting a multicomponent model rather than a single core-Sérsic model over the entire radial range provides a more reliable estimate of the core size (Dullo & Graham 2014;Dullo 2019). Measured core sizes for massive ellipticals -derived in this way -are typically tens to a few hundred parsecs (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations